Extensive Limb Lengthening for Achondroplasia and Hypochondroplasia - Dror Paley (MDPI AG, 2021)
Extensive limb lengthening (ELL) was completed in 75 patients: 66 achondroplasia and 9 hypochondroplasia. The average lengthening was 27 cm for achondroplasia (12-40 cm) and 17 cm for hypochondroplasia (range 10-25 cm). There were 48 females and 27 males. Lengthening was done either by 2-segment (14 patients; both tibias and/or both femurs) or by 4-segment lengthenings (64 patients; both femurs and tibias at the same time). Most patients also had bilateral humeral lengthening. Patients had 2 or 3 lower limb lengthenings and one humeral lengthening. Lengthenings were either juvenile-onset (31), adolescent-onset (38) or adult-onset (6). The average age at final follow-up was 26 years old (range 17-43 years). There were few permanent sequelae of complications. The most serious was one paraparesis. All patients returned to activities of normal living and only one was made worse by the surgery (paraparesis). This is the first study to show that ELL can lead to an increase of height into the normal height range. Previous studies showed mean increases of height of up to 20 cm, while this study consistently showed an average increase of 30 cm (range 15-40 cm) for juvenile-onset and mean increase of 26 cm (range 15-30 cm) for adolescent-onset. This results in low normal height at skeletal maturity for males and females. The adult-onset had a mean increase of 16.8 (range 12-22 cm). This long-term follow-up study shows that ELL can be done safely even with large lengthenings and that 4-segment lengthening may offer advantages over 2-segment lengthening. While all but the more recent cases were performed using external fixation, implantable limb lengthening promises to be an excellent alternative and perhaps an improvement.